INVESTIGATION OF PERCEIVED RISKS IN HOLIDAY PURCHASES FROM WEB-BASED TRAVEL INTERMEDIARIES ACCORDING TO DEMOGRAPHIC CHARACTERISTICS - Aksoz, Emre Ozan; Hafif, Furkan (The European Journal of Applied Economics, 2025)
The main purpose of this research is to determine the risks in holiday purchasing that tourists perceive in the preferences of web-based travel agencies and risk reduction strategies. The data of the research were obtained from domestic tourists who residing in Eskisehir and previously purchased holiday. A total of 406 questionnaires were accepted as valid as a result of the face-to-face questionnaires. The higher perceived risk dimensions by tourists were determined as performance risk, security risk and financial risk. The tourists who purchase a holiday from a sales office of travel agency, females, singles, in the age group of 18-25 and 50 and over, higher perceived risk than others. Based on the results of the research, suggestions were made to practitioners in the sector and researchers.
Keywords: Perceived Risk, E-Holiday Purchases, Web-Based Travel Agencies.